Kemampuan Siswa Kelas X SMA Sentosa Bhakti Baturaja Menentukan Frasa Adjektival dalam Paragraf Deskriptif - Rita Nilawijaya; Awalludin Awalludin; Henny Nopriani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2023)
The purpose of this study was to describe the ability of students of class X SMA Sentosa Bhakti Baturaja determine adjective phrases in the descriptive paragraphs. The population in this study were all students of class X SMA Sentosa Bhakti Baturaja by the number of 39 students, the sample size of 39 students. The method used in this research is descriptive method. Data collection techniques are objective testing and data analysis techniques are descriptive qualitative data analysis techniques. Based on the results of research and discussion, it can be concluded that Traditionally, the average percentage of high school students' skills class X SMA Sentosa Bhakti Baturaja in determining phrase descriptive adjectives in the paragraph above the 66 scored as many as 23 people or 74.36%. Meanwhile, students who receive an excellent rating categories as many as 12 people or 30.77%, well as many as 17 people or 43.59%, quite as much as 3 or 7.69%, much less 4 people or 10.26%, and very less as much as 3 or 7.69%. Thus, it can be concluded that the students of class X SMA Sentosa Bhakti Baturaja was able to determine the adjective phrase descriptive paragraphs well. Therefore, it is recommended that no further research effort to make this study for comparison.